Examining Trauma-Related Shame and Trauma Coping Self-Efficacy as Predictors of PTSD in Women in Jail - Shannon M. Lynch; Stephanie Kaplan (Social Sciences)
Women in jail experience high rates of exposure to interpersonal violence and PTSD. However, programming to address women’s trauma-related treatment needs in corrections facilities is limited and this population remains underserved. Research identifying treatment targets to reduce PTSD symptoms and to support recovery is needed. Prior research suggests trauma-related shame and coping self-efficacy are associated with PTSD symptoms in the general population. The present study aimed to expand upon the current literature by using structural equation modeling to evaluate the associations among cumulative interpersonal violence exposures, trauma coping self-efficacy (TCSE), trauma-related shame, and current PTSD symptoms in a sample of randomly selected women in jail (n = 150). Over half the sample (55%) reported clinically significant PTSD symptoms. Shame (β = 0.372, p = 0.001) and TCSE (β = −0.375, p < 0 000) significantly predicted PTSD symptoms, explaining 50% of the variance in PTSD. These findings provide preliminary direction for identification and implementation of evidence-based treatments addressing trauma-related shame and TCSE to reduce PTSD symptoms in incarcerated women.